BZP-'Party pills', populism and prohibition: Exploring global debates in a New Zealand context. Issue 2 (June 2017) - Hutton, Fiona
In New Zealand, the debates surrounding legal highs have been developing for approximately a decade. New Zealand's historical grappling with the problem of legal highs reflects a global problem in addressing the issues related to new psychoactive substances. The focus of this article is the prohibition of BZP-based party pills under the Misuse of Drugs (Classification of BZP) Amendment Act, 2008 (hereafter the 2008 Act). This article reports on a qualitative study of the banning of BZP-based party pills in New Zealand, using thematic analysis of the discourses contained in the 2007 Parliamentary Bill readings of the 2008 Act. Six key themes were identified from the bill readings: prohibition is not an effective way to deal with drug use; BZP has a 'gateway effect'; availability and accessibility means young people can access BZP-PPs too readily; young people are at risk; BZP has contributed to establishing a pill popping culture in New Zealand; and BZP has the potential for harm/has a moderate risk of harm. The thematic analysis revealed that evidence was often not fully represented in parliamentary debates, and that many of the concerns raised about BZPPs could have been dealt with through regulation rather than prohibition. A punitive moral populism aimed at drug use and drug users was also identified, driven by fears of drug using groups, and the symbolism associated with drug use.